Air pollution, physical activity and ischaemic heart disease: a prospective cohort study of interaction effects - Bertil Forsberg; Johan Nilsson Sommar; Wasif Raza; Benno Krachler (BMJ Open)
Objective To assess a possible interaction effect between physical activity and air pollution on first incidence of ischaemic heart disease (IHD).Design Prospective cohort study.Setting Umeå, Northern Sweden.Participants We studied 34 748 adult participants of Västerbotten Intervention Programme cohort from 1990 to January 2014. Annual particulate matter concentrations (PM2.5 and PM10) at the participants’ residential addresses were modelled and a questionnaire on frequency of exercise and active commuting was completed at baseline. Cox proportional hazards modelling was used to estimate (1) association with physical activity at different levels of air pollution and (2) the association with particulate matter at different levels of physical activity.Outcome First incidence of IHD.Results Over a mean follow-up of 12.4 years, there were 1148 IHD cases. Overall, we observed an increased risk of IHD among individuals with higher concentrations of particles at their home address. Exercise at least twice a week was associated with a lower risk of IHD among participants with high residential PM2.5 (hazard ratio (HR) 0.60; 95% CI: 0.44 to 0.82) and PM10 (HR 0.55; 95% CI: 0.4 to 0.76). The same beneficial effect was not observed with low residential PM2.5 (HR 0.94; 95% CI: 0.72 to 1.22) and PM10 (HR 0.99; 95% CI: 0.76 to 1.29). An increased risk associated with higher long-term exposure to particles was only observed among participants that exercised in training clothes at most one a week and among those not performing any active commuting. However, only the interaction effect on HRs for exercise was statistically significant.Conclusion Exercise was associated with a lower risk of first incidence of IHD among individuals with higher residential particle concentrations. An air pollution-associated risk was only observed among those who exercised less. The findings support the promotion of physical activity and a mitigation of air pollution.